Risks in international bank lending : first report of the International Banking Study Group of the Group of Thirty - Group of Thirty; Bell, Geoffrey (New York : Group of Thirty, 1982)
The purpose of this study is to discuss the greater risks that may have arisen in the course of the rapid growth in international bank lending during the 1970s and to make suggestions aimed at strengthening the capacity of the system to manage those risks. It focusses on three areas- country risk and the rescheduling of sovereign debt; maturity transformation and the interbank market as well as the handling of distressed bank.
Includes bibliographical references.
usc 28/09/2018
Loans
Keywords: Loans, Foreign; Banks and banking, International